Relationships between physical therapy intervention and opioid use: A scoping review. Issue 7 (14th August 2021) - Brown‐Taylor, Lindsey; Beckner, Aaron; Scaff, Katie E.; Fritz, Julie M.; Buys, Michael J.; Patel, Shardool; Bayless, Kim; Brooke, Benjamin S.
Abstract: Objective: To synthesize available evidence that has examined the relationship between physical therapy (PT) and opioid use. Type: Scoping Review Literature Survey: Data sources including Google Scholar, Embase, PubMed, Cochrane Library, and CINAHL were searched for English articles up to October 24, 2019 using terms ("physical therapy"[Title/Abstract] OR physiotherapy[Title/Abstract] OR rehabilitation[Title/Abstract]) AND (opiate*[Title/Abstract] OR opioid*[Title/Abstract]). Methodology: Included studies evaluated a PT intervention and reported an opioid‐use outcome. Data were extracted to describe the PT intervention, patient sample, opioid‐use measurement, and results of any time or group comparisons. Study quality was evaluated with Joanna Briggs checklists based on study design. Synthesis: Thirty studies were included that evaluated PT in at least one of these seven categories: interdisciplinary program (n = 8), modalities (n = 3), treatment (n = 3), utilization (n = 2), content (n = 3), timing (n = 13), and location (n = 2). Mixed results were reported for reduced opioid‐use after interdisciplinary care and after PT modalities. Utilizing PT was associated with lower odds (ranging from 0.2–0.8) of using opioid medication for persons with low back pain (LBP) and injured workers; however, guideline‐adherent care did not further reduce opioid use for persons with LBP. Early PT utilization after index visit for spine or joint pain and after orthopedic surgery was also associated with lower odds of using opioid medications (ranging from 0.27–0.93). Emergency department PT care was not associated with fewer opioid prescriptions than standard emergency department care. PT in a rehabilitation center after total knee replacement was not associated with lower opioid use than inpatient PT. Conclusions: The relationship between timing of PT and opioid use was evaluated in 13 of 30 studies for a variety of patient populations. Eight of these 13 studies reported a relationship between early PT and reduced subsequent opioid use, making the largest sample of studies in this scoping review with supporting evidence. There is limited and inconclusive evidence to establish whether the content and/or location of PT interventions improves outcomes because of heterogeneity between studies.